A Shield to Legitimize Virtually Any Content: Tracking the Video Game Lobby's Political Economic Power. (25th March 2015) - Proffitt, Jennifer M.; Susca, Margot A.
Abstract: In 2011, the U.S. Supreme Court in Brown v. Entertainment Merchants Association overturned a California law that sought to keep violent video games away from minors. Entertainment Software Association (Esa), the video game industry's trade organization, for years fought legislation aimed at providing parents with more information about extremely violent games. This article analyzes campaign finance records, lobbying reports, trade publications, and court documents to illustrate how Esa uses its power to influence the U.S. regulatory, legislative, and judicial process. By documenting this political economic influence, this article charts interrelated developments regarding the consolidation of ownership and growth of the corporate video game lobby and assesses how Esa political contributions marginalize the public's access to information about violent games .